Effects of Mango Mistletoe (Dendrophthoe pentandra L. Miq) Extracts on Brain in Hypertensive Rats Treated with Deoxycorticosterone Acetate (DOCA)-Salt - Saputri, Syntia Diyah Hayu Ria; Sjakoer, Nour Athiroh Abdoes; Mubarakati, Nurul Jadid (JSMARTech: Journal of Smart Bioprospecting and Technology, 2021)
Mango mistletoe (Dendrophthoe pentandra) is a plant that has the potential as a medicinal plant. Mango mistletoe is reported to contain the flavonoids quercetin, mesoinositol, rutin, and tannins. Hypertension as a non-communicable disease is a very serious health problem experienced by people in developing countries. Hypertension can be caused by high ROS (reactive oxygen species) which can inhibit oxygen flow to the heart and brain. Antioxidants can reduce the risk of hypertension. Damage to the brain due to hypertension is manifest in the white matter area. This study aimed to see how the histopathological profile of the brain in hypertensive rats (DOCA-Salt) which were given mango mistletoe methanolic extract (MMME) by experimental method. The number of tested animals was 25 male Wistar rats divided into 5 groups, each group contained 5 rats, they were negative control (Control-) as normotension, positive control (Control+) as inducer, and the treatment group with the provision of MMME at a dose of 50 mg / kgBW, 100 mg / kgBW, and 200 mg / kgBW. Data were analyzed using JAMOVI 1.1.9.0. Based on the results of the study showed that the difference in significant values between all groups was p<0.05. So, that giving EMBM to male rat significantly can decrease the number of cell necrosis and affect the width of the white matter area of the brain. The three dose variations did not show a significant difference, so this effect was controlled by the MMME dose of 50 mg / KgBW which was the optimum dose in reducing the amount of cell necrosis in the white matter area of the male Wistar rat brain.